Identification and Characterization of Two Novel Compounds: Heterozygous Variants of Lipoprotein Lipase in Two Pedigrees With Type I Hyperlipoproteinemia - Wang, Shuping; Cheng, Yiping; Shi, Yingzhou; Zhao, Wanyi; Gao, Ling; Fang, Li; Jin, Xiaolong; Han, Xiaoyan; Sun, Qiuying; Li, Guimei; Zhao, Jiajun; Xu, Chao (Frontiers in Endocrinology, 2022)
Background: Type I hyperlipoproteinemia, characterized by very severe hypertriglyceridemia, is mainly caused by the loss-of-function mutation of lipoprotein lipase (LPL) gene. So far, there have been more than 200 mutations in LPL gene reported and only a limited number of mutations have been evaluated the pathogenesis. Objective: To explore the molecular mechanisms underlying the lipoprotein lipase deficiency in two pedigrees with type 1 hyperlipoproteinemia. Methods: We conducted the systematic clinical and genetic analysis of two pedigrees with type 1 hyperlipoproteinemia. Post-heparin plasma of all the members was used for the LPL activity analysis. In vitro studies were performed in HEK-293T cells which were transiently transfected with wild type or variant LPL plasmid. Furthermore, the production and activity of LPL was analyzed in cell lysates or culture medium. Results: Proband 1 developed acute pancreatitis in youth and her serum triglyceride (TG) continued to be at an ultra-high level, although the application of various lipid-lowering drugs. Proband 2 was diagnosed with type 1 hyperlipoproteinemia at 9 months of age and his serum TG levels were mildly elevated with treatment. Two novel compound variants of LPL (c.3G>C, p.M1? and c.835_836delCT, p. L279Vfs*3, c.188C>T, p. Ser63Phe and c.662T>C, p. Ile221Thr) were identified respectively in two probands. The post-heparin LPL activity of proband 1 and 2 showed a decrease of 75.09% and 57.29% compared with the control. In vitro studies showed that a substantial reduction in the expression, secretion, or enzyme activity of LPL in all the LPL variants. Conclusions: Two novel compound variants of LPL induced the function defects of LPL and caused type I hyperlipoproteinemia.